Assessment of the Effectiveness of Using Magnoimmunosorbents for the Selective Concentration of Anthrax Agent Spores - F. V. Logvin; O. V. Semenova; A. G. Ryazanova; I. V. Zharnikova; L. Yu. Aksenova; D. V. Rusanova; S. A. Kurcheva; O. L. Startseva; A. S. Geogdzhayan; A. N. Kulichenko (Проблемы особо опасных инфекций, 2023)
The aim of the study was to assess the effectiveness of the developed anthrax magnoimmunosorbents (MIS) for the selective concentration of Bacillus anthracis spores and to increase the sensitivity of anthrax agent detection techniques, including when testing soil samples.Materials and methods. We used 10 vaccine strains of B. anthracis and 30 strains of closely related bacilli of the genus Bacillus (B. cereus – 15, B. thuringiensis – 10, B. megaterium – 5) with typical species properties. The work was performed on three experimental batches of magnoimmunosorbents. DNA extraction and PCR setting was carried out in compliance with the instructions for reagent panel for B. anthracis DNA detection “ApliSens Bacillus anthracis-FRT”.Results and discussion. It is shown that when using MIS, the sensitivity of the cultural method is increased by at least 7 times (taking into account the possibility of sorption of 1–10 or more spores on a sorbent particle). The sensitivity of the PCR method is improved by 10 times and amounts to 50 B. anthracis spores per 1 ml for the samples concentrated with the help of MIS. The sensitivity of the bacteriological method using MIS increases by a factor of 7.5 when testing the artificially contaminated with B. anthracis soil samples. Hence, application of the developed MIS makes it possible to significantly enhance the sensitivity of anthrax agent detection methods and can be considered as an effective means of sample preparation for the investigation of environmental objects (soil).